Long Term Mortality Risk in Individuals with Atrial or Ventricular Premature Complexes– Results From The Third National Health And Nutrition Examination Survey (NHANES III) - Qureshi, Waqas (Am J Cardiol, 2014)
Premature ectopic beats are frequently detected on routine 12-lead screening-electrocardiogram (ECG). However, their prognostic importance in individuals without known cardiovascular disease (CVD) is not well established. We evaluated prognostic value of atrial premature complexes (APC’s) and ventricular premature complexes (VPC’s) detected by a single 12-lead-ECG. A prospective cohort of 7504 participants selected from nationally-representative, community-dwelling individuals living in United States, enrolled in the Third Health and Nutrition Examination Survey (NHANES-III) from 1988 – 94 with follow up through December 2006 without known CVD. The main outcomes were all – cause mortality, CVD related mortality and IHD related mortality. Out of 7504 participants (mean age 60 ± 14 years, 47% women, 49% whites), 89 (1.2%) had APC’s and 110 (1.5%) had VPC’s on 12 – lead ECG. During a follow up of up to 18 years, 2386 deaths occurred, of which 963 were due to CVD and 511 were due to IHD. In a multivariable adjusted for demographics, clinical variables and ECG measures, APC’s were significantly associated with all-cause mortality [HR, 1.41 (95% CI, 1.08–1.80)], CVD death [HR, 1.78 (95% CI, 1.26–2.44)] and IHD death [HR, 2.40 (95% CI, 1.59–3.47)]. For VPCs, however, there were no significant associations with all – cause mortality [HR, 1.05 (95% CI, 0.80–1.36)], CVD death [HR, 0.96 (95% CI, 0.62–1.43)] and IHD death [HR, 0.89 (95% CI, 0.47–1.52)]. In conclusion, APC’s, but not VPC’s, on routine screening ECG are predictive of adverse events in community-dwelling individuals without known CVD.